Predšolsko obdobje in nadarjenost - Hmelak, Maja; Zupančič, Tomaž; Muhič, Miran; Bratina, Tomaž (University of Maribor Press, 2025)
Preschool Period and Giftedness. Preschool children differ in abilities, knowledge, and skills, and their development progresses at varying intensities across different domains. Early identification and addressing of areas of giftedness are crucial to create conditions that allow children to develop optimally. The environment in which children grow plays a significant role, stimulating their intellectual, social, and motor development. Special emphasis is placed on creativity, which is most often expressed through art, movement, and play. Modern approaches in preschool education also integrate information and communication technologies, fostering computational thinking in children. During this period, it is essential to provide appropriate challenges and adult support to potentially gifted children. With proper guidance and pedagogical approaches, children can realize their full potential.